Higher Serum CCN3 Is Associated with Disease Activity and Inflammatory Markers in Rheumatoid Arthritis - Yingying Wei; Linan Peng; Yi Li; Na Zhang; Ke Shang; Lihua Duan; Jixin Zhong; Jie Chen (Journal of Immunology Research)
Nephroblastoma overexpressed protein (NOV/CCN3), the early discovered member of the CCN family, has recently been suggested to be involved in a number of inflammatory processes, including wound healing, alveolar epithelial cell inflammation, cancer metastasis, and macrophage foam cell formation. However, the role of CCN3 in rheumatoid arthritis (RA), a classic autoimmune and inflammatory disease, remains elusive. RA is a chronic systemic autoimmune disease that eventually leads to cartilage and bone destruction and joint dysfunction. In this study, we investigated the potential of serum CCN3 as a biomarker for RA. The serum levels of CCN3 were measured by ELISA. The clinical and laboratory parameters were collected from a clinical record system, and disease activity was determined by joint disease activity score 28 (DAS28). Our results showed that the serum levels of CCN3 were significantly increased in RA patients compared to healthy controls. Furthermore, the CCN3 level was positively correlated with DAS28 (CRP), DAS28 (ESR), and the level of anti-CCP Ab, an autoantibody highly specific for RA. Furthermore, CCN3 showed a positive correlation with inflammatory cytokine IL-6, while no significant correlation with TNF-α was observed. These data suggest that CCN3 plays an important role in the development of RA and might be a potential disease activity biomarker for RA.